2014
DOI: 10.1103/physreve.89.022306
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Janus particles confined in a channel

Abstract: Janus particles present an important class of building blocks for directional assembly. These are compartmentalized colloids with two different hemispheres. Here, we consider a two-dimensional model of Janus disks consisting of a hydrophobic semicircle and an electro-negatively charged one. Placed in a solution, the hydrophobic sides will attract each other while the charged sides will give rise to a repulsive force. Using molecular dynamics simulations, we study the morphology of these particles when confined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that confinement can tune the self-assembly of polyhedral nanoparticles, patchy spherical colloids, asymmetric and symmetric dumbbells, , surfactants and polymers, and soft hydrogel nanoparticles . New lamellae structures were observed for Janus dumbbells confined between parallel plates. , Particularly, the confinement using nanotubes has been employed to study the morphologies of self-assembled clusters of lipid and cholesterol, surfactants, , diblock copolymers, and triblock and spherical Janus nanoparticles. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that confinement can tune the self-assembly of polyhedral nanoparticles, patchy spherical colloids, asymmetric and symmetric dumbbells, , surfactants and polymers, and soft hydrogel nanoparticles . New lamellae structures were observed for Janus dumbbells confined between parallel plates. , Particularly, the confinement using nanotubes has been employed to study the morphologies of self-assembled clusters of lipid and cholesterol, surfactants, , diblock copolymers, and triblock and spherical Janus nanoparticles. …”
Section: Introductionmentioning
confidence: 99%
“…Most researches on the magnetic interaction and self-assembly of Janus particles rely on experimentation. Even though modeling and simulation are employed to investigate the self-assembly and the dynamics of Janus particles [26][27][28][29][30][31], further studies are still required to understand the magnetic interaction lying behind the formation of various self-assembly structures and the fluid flow induced by the actuated particles. Direct numerical simulation schemes [32][33][34][35][36][37], which have been developed to solve particulate flows with isotropic magnetic particles, are promising options in tackling particulate flows with Janus magnetic particles if they are enhanced to take into account the magnetic anisotropy of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Using molecular dynamics simulations, Sobrino Fernandez et al studied the selfassembly phenomenon of Janus particles when confined in a channel. [21]. Ghosh et al investigated self-propelled over damped microswimmers in a two dimensional periodically compartmentalized channel and proved that ratcheting of Janus particles can be orders of magnitude stronger than for ordinary thermal potential ratchets [22].…”
Section: Introductionmentioning
confidence: 99%